Concept and Measurement Results of Two Decentralized Solar Thermal Feed-in Substations. (September 2018) - Heymann, M.; Rosemann, T.; Rühling, K.; Tietze, T.; Hafner, B.
Abstract: Decentralized feed-in of solar thermal gains can contribute to the decarbonisation and flexibilisation of modern district heating networks. This paper presents the design, the control concept and measurement results of two solar thermal feed-in substations. Recommendations for future network feed-in substation are derived by analyzing and comparing the operation behavior as well as energy flows. The method used to analyze the different substations and the used characteristic performance parameters are introduced.